2008
DOI: 10.1590/s0103-90162008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the soil physical quality of a tropical oxisol using the S index

Abstract: Soil physical quality is fundamental for the sustainability of agro ecosystems. Soil physical quality assessment must be developed using parameters that describe physical behavior. S, a new soil physical parameter has recently been introduced for assessing the soil physical quality. A good soil physical quality has been associated with values of S > 0.035 in soils from temperate climates. However, S has not been evaluated in tropical soils yet. Therefore we tested the hypothesis that S is a reliable soil physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
2
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 16 publications
5
26
2
12
Order By: Relevance
“…Adjustment equations of macroporosity (MP) and total porosity (TP) as a function of the S index in the areas under no-tillage for eight years (NT8), no-tillage for four years (NT4), conventional tillage for two years (CT2), pasture, and forest that more than 72 % of the samples of an Oxisol under conventional tillage showed values of S> 0.035, and for no-tillage 55 % of the samples. These results demonstrate the great potential of the S index to identify variations in the soil quality of different tillage systems (Tormena et al, 2008). Noventa et al (2006) reported higher S indices in no-tillage soil with oats, due to the thin and aggressive root system that creates a series of long and thin channels resulting in better functionality to the soil structure.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Adjustment equations of macroporosity (MP) and total porosity (TP) as a function of the S index in the areas under no-tillage for eight years (NT8), no-tillage for four years (NT4), conventional tillage for two years (CT2), pasture, and forest that more than 72 % of the samples of an Oxisol under conventional tillage showed values of S> 0.035, and for no-tillage 55 % of the samples. These results demonstrate the great potential of the S index to identify variations in the soil quality of different tillage systems (Tormena et al, 2008). Noventa et al (2006) reported higher S indices in no-tillage soil with oats, due to the thin and aggressive root system that creates a series of long and thin channels resulting in better functionality to the soil structure.…”
Section: Resultsmentioning
confidence: 70%
“…Oliveira et al (2000) observed an increased bulk density after 17 years of grazing, which was however not significantly correlated with forage production. However, the pasture restoration benefits the soil structure, similarly as no-till systems improve it by OM accumulation (Colet, 2006) The influence of management on soil physical quality has been studied based on a number of physical properties, e.g., bulk density, soil moisture and penetration resistance, and even combined in the Least Limiting Water Range, and more recently, in Brazil, the S index (Machado, 2006;Tormena et al, 2008). This S index has been proposed as an indicator of the soil physical and structural quality, and is based on the parameters of the water retention curve in the soil (Dexter, 2004a, b, c).…”
Section: Introductionmentioning
confidence: 99%
“…Mohanty et al (1996) showed that water infiltration rate was highest in crop rows, while da Silva et al (1997) reported soil physical differences between row and inter-row zones. Tormena et al (2008) also found better soil physical quality within crop rows. What appears to be unknown is how soil physical properties change with lateral distance from the crop row due to both the intensity of soil disturbance by furrow opening and plant root growth.…”
Section: Introductionmentioning
confidence: 83%
“…Management practices applied to a soil over a time period can affect some of its physical properties which can be degraded due to the use of agricultural mechanization (Tormena et al, 2008), affecting runoff velocity and water erosion (Bertol et al, 1997;Cogo et al, 1983). Thus, each management practice causes additional effects on this surface roughness, especially related to mechanical till (Zoldan Júnior et al, 2008).…”
Section: Introductionmentioning
confidence: 99%